A new tool for practitioner-led evaluation of teacher professional development - McChesney, K.; Aldridge, Jill (Routledge, 2018)
© 2018 Teacher Development Schools and education systems are being challenged to improve the evaluation of teacher professional development, yet there is a lack of practical tools for doing so. This article describes the development and validation of a new instrument to assess teachers’ perceptions of the impact of professional development. This instrument, designed to be time- and cost-effective, was theoretically grounded and, as evidenced by the results reported in this article, psychometrically sound. The instrument was completed twice (examining different types of professional development) by 393 teachers. The results for both data-sets demonstrated a strong factor structure with good internal consistency for all scales. Further data analysis indicated that the scales could effectively distinguish between the experiences of different groups of teachers. The finalised instrument, named the Impact of Teacher Professional Development Questionnaire, is presented in full, and the practical advantages and limitations of the instrument are discussed.